DEFORMATION CRITERION OF OPTIMIZATION OF ROUTES OF THIN HIGH-CARBON WIRE DRAWING - Yu. L. Bobarikin; S. V. Avseykov; A. V. Vedeneyev; I. N. Radjkova (Литьë и металлургия)
The deformation criterion of assessment for optimization of the wire drawing routes of thin high-carbon wire, enabling to increase plastic properties of wire is offered.